1996
DOI: 10.1002/(sici)1099-0992(199609)26:5<763::aid-ejsp791>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Degrading situations and antisocial behaviour: an experimental approach to delinquency

Abstract: INTRODIJCTIONAre we all likely to behave contrary to our morality or to commit illegal acts? This seems probable if we refer to past studies in social psychology. Milgram's subjects (Milgram, 1974) gave a 'lethal' reinforcement simply when ordered to do so by a 'scientific authority'. The 'guards' in Zimbardo's classic prison study (1 969) readily acted as torturers. However, the majority of criminological approaches to delinquency' (biological, psychological or sociological) are based on the implicit postulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…A few laboratory findings are compatible with a dependency interpretation of maltreatment effects. Van Duuren and Di Giacomo (1996, 1997) also uncovered a link between harsh treatment and dependency across several experimental studies. These researchers reported that undergraduates who experienced public failure were not only more eager to affiliate, they were also more vulnerable to social influence (Van Duuren & Di Giacomo, 1996, 1997).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…A few laboratory findings are compatible with a dependency interpretation of maltreatment effects. Van Duuren and Di Giacomo (1996, 1997) also uncovered a link between harsh treatment and dependency across several experimental studies. These researchers reported that undergraduates who experienced public failure were not only more eager to affiliate, they were also more vulnerable to social influence (Van Duuren & Di Giacomo, 1996, 1997).…”
Section: Discussionmentioning
confidence: 91%
“…The socialemotional bonds that result increase vulnerability to social influence and indoctrination (Baron, 2000;Dolinski et al, 2002;Van Duuren & Di Giacomo, 1996, 1997 and foster a depersonalized, social identity (Baron, 2000;Hogg, 2001;Rosenblatt, 1964). At the same time, maltreatment signals differential power: The depersonalized individual's dependence on the group is not matched by any dependence the group has on individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations